2020
DOI: 10.1155/2020/8573817
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Falling, Lower Extremity Strength, and Physical and Balance Performance in Older Adults with Diabetes Mellitus

Abstract: Fear of falling (FoF) is known to affect the physical activities and quality of life of older adults with type 2 diabetes mellitus (DM). Many complications of DM, especially ones distressing lower extremity (LE), could lead to increased fall risk and FoF. This study aimed to explore the relationship between FoF, LE muscle strength, and physical performance in older adults without diabetes mellitus (ONDM) and with DM (ODM) with varying degrees of balance impairment. The participants comprised 20 ONDM and 110 OD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…Further, Renata et al reported that advanced age, absence of proprioceptive sense assessed by a 128 Hz tuning fork, disability, and absence of step strategy were associated with abnormal balance and mobility in elderly patients with type 2 DM [ 52 ]. Although there is a debate over whether the strength of the lower extremities affects balance ability in older people [ 53 , 54 , 55 ], lower extremity muscle strength of diabetic patients also affected the TUG test results in our study. The loss of muscle strength in these patients may have a significant impact on TUG test results, not on BBS.…”
Section: Discussionmentioning
confidence: 77%
“…Further, Renata et al reported that advanced age, absence of proprioceptive sense assessed by a 128 Hz tuning fork, disability, and absence of step strategy were associated with abnormal balance and mobility in elderly patients with type 2 DM [ 52 ]. Although there is a debate over whether the strength of the lower extremities affects balance ability in older people [ 53 , 54 , 55 ], lower extremity muscle strength of diabetic patients also affected the TUG test results in our study. The loss of muscle strength in these patients may have a significant impact on TUG test results, not on BBS.…”
Section: Discussionmentioning
confidence: 77%
“…Fall efficacy or balance confidence, which defined as a person's belief of their ability to maintain balance, were known to affect the quality of life and physical activities of older adults with T2DM. 48,49 Fear of falling, lower limb strength and physical performance were more influenced when the balance function decreased. 48 A comprehensive treatment for increasing T2DM patients balance capacity should include assessment of balance performance and balance confidence.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Fear of falling, lower limb strength and physical performance were more influenced when the balance function decreased. 48 A comprehensive treatment for increasing T2DM patients balance capacity should include assessment of balance performance and balance confidence. The pooled results of our review demonstrated that exercise intervention group had no significant improvements of fall efficacy compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, type 2 DM (T2DM) is known to be directly linked to the lifestyle factors and becomes a key health issue due to various complications [ 1 ]. Some of the common complications such as the peripheral neuropathy and retinopathy are well documented in their contributions to falling [ 2 ] and fear of falling [ 3 ] and significantly degrade the quality of life [ 1 ]. Moreover, these complications were reportedly impacting increased disability, lost productivity, mortality, and amplified health-care costs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%